The Four Stages of Highly Effective Crisis Management : How to Manage the Media in the Digital Age - Jordan-Meier, Jane (CRC Press, 2016)
From the Japanese tsunami and the Egyptian revolution to the Haitian earthquake and the Australian floods, social media has proven its power to unite, coalesce, support, champion, and save lives. Presenting cutting-edge media communication solutions, The Four Stages of Highly Effective Crisis Management explains how to choose the appropriate language and media outlet to properly convey your message during and after a crisis. Unveiling the secrets of how to manage the media in a crisis, the book examines how rapidly evolving social media and Web 2.0 technologies have changed the crisis management landscape. It illustrates the four distinct stages of media reporting during a crisis and details the information that must be provided. The author provides readers with a wealth of helpful tips and tools--including guidelines, checklists, and case studies that illustrate best practices in crisis media management. Divided into five sections, the book: Examines how the kingdom of news has changed and considers the new hybrid model that is emerging Identifies the four distinct stages in which both old and new media report a crisis Addresses the use of spokespeople according to the four stages, as well as when to use the chief executive officer Discusses media interviews, including how to handle news conferences, bloggers, and the importance of media training Considers the communication aspects of crisis management--including how to harness the power of Facebook, Twitter, YouTube, Digg, Wikipedia, Flickr, and social media releases The book's resource-rich appendices include a checklist for briefing a spokesperson, sample media release, a step-by-step flowchart for creating a crisis communication plan, and social media policy guidelines. Complete with a detailed guide on what tools to use and when to use them, this book provides the techniques and understanding required to communicate effectively and avoid any potential bad press and embarrassment that could result from information mismanagement. Jane Jordan-Meier was interviewed about leadership in a crisis and the stages of a crisis in the wake of the Murdoch phone-hacking scandal. She also discusses crisis management planning in The Sydney Morning Herald and in Daily Ovation. She was interviewed in August 2011 by Globe and Mail. Discover more about the book, including a video of the author explaining how to turn media questions into gold and visit smallbusinessadvocate.com for a series of recent interviews. Jane Jordan-Meier appeared in a video interview with Crisis Manager Melissa Agnes on July 3, 2012.